Increased Serum Immunoglobulin A Antiphospholipid Antibody Levels in Childhood Henoch-Schönlein Purpura - Özgün BAŞARAN KAYA,; Mahmut ÇİVİLİBAL,; Murat ELEVLİ,; Macit KOLDAŞ,; Nilgün SELÇUK DURU1, (Archives of Rheumatology, 2012)
Objectives: This study aims to investigate the possible role of serum immunoglobulin A (IgA) anti-phospholipid antibodies (aPL) in childhood Henoch-Schönlein purpura (HSP). Patients and methods: Thirty children with HSP (12 boys, 18 girls; mean age 9.0±3.1 years; range 4 to 16 years) and 30 healthy children who were age and gender-matched were enrolled in this study. In addition to the levels of serum immunoglobulins, acute phase reactants, and other biochemical parameters, serum IgA class anti-cardiolipin antibodies (IgA aCL) and IgA class anti-b2- glycoprotein I antibodies (IgA ab2-GPI) were measured. Blood samples from these patients were collected at both the acute and convalescent stages, and the IgA aCL and IgA ab2-GPI antibodies were measured by enzyme-linked immunosorbent assay (ELISA). Results: Serum IgA aCL and IgA ab2-GPI levels were significantly higher in children with HSP than in the controls (2.12±0.56 U/mL versus 1.57±0.31 U/mL, p<0.001 and 2.32±1.84 U/mL versus 0.69±0.64 U/mL, p<0.001, respectively). The levels of these antibodies decreased significantly in the remission stage of the disease. In the regression analysis, the serum IgA level was the only independent predictor of the increased IgA aCL and IgA ab2-GPI antibodies (b: 0.549, p=0.002 and b: 0.595, p=0.001, respectively). Conclusion: The study results suggested that serum levels of IgA aCL and IgA ab2-GPI antibodies are elevated in the active stage of pediatric HSP, indicating that anti-phospholipid antibodies may play a role in the onset of disease. Therefore, we believe that the levels of serum anti-phospholipid antibodies may be an indicator of childhood HSP activity.